Ground state of a spin-1/2 Heisenberg-Ising two-leg ladder with XYZ intra-rung coupling - Verkholyak, T.; Strečka, J. (Condensed Matter Physics, 2013)
The quantum spin-1/2 two-leg ladder with an anisotropic XYZ Heisenberg intra-rung interaction and Ising inter-rung interactions is treated by means of a rigorous approach based on the unitary transformation. The particular case of the considered model with X-X intra-rung interaction resembles a quantum compass ladder with additional frustrating diagonal Ising interactions. Using an appropriately chosen unitary transformation, the model under investigation may be reduced to a transverse Ising chain with composite spins, and one may subsequently find the ground state quite rigorously. We obtain a ground-state phase diagram and analyze the interplay of the competition between several factors: the XYZ anisotropy in the Heisenberg intra-rung coupling, the Ising interaction along the legs, and the frustrating diagonal Ising interaction. The investigated model shows extraordinarily diverse ground-state phase diagrams including several unusual quantum ordered phases, two different disordered quantum paramagnetic phases, as well as discontinuous or continuous quantum phase transitions between those phases. Квантову спiн-1/2 двоногу драбинку з анiзотропною XY Z взаємодiєю Гайзенберґа вздовж щаблiв i Iзинґовою взаємодiєю мiж спiнами на сусiднiх щаблях розглянуто в межах строгого пiдходу, який ґрунтується на унiтарному перетвореннi. Частковий випадок моделi з X–X взаємодiєю вздовж щаблiв вiдображає модель квантового компасу на драбинцi з додатковими дiагональними Iзинґовими взаємодiями. Використовючи унiтарне перетворення, модель можна звести до поперечного ланцюжка Iзинґа з композитними спiнами, i як наслiдок основний стан можна знайти строго. Ми отримуємо фазову дiаграму основного стану i аналiзуємо взаємовплив конкуренцiї кiлькох факторiв: XY Z анiзотропiї взаємодiї Гайзенберґа, Iзинґової взаємодiї вздовж ланцюжкiв та фрустрованої дiагональної Iзинґової взаємодiї. Розглянута модель демонструє складнi фазовi дiаграми основного стану, включаючи декiлька нетипових квантових впорядкованих станiв, два рiзних невпорядкованих квантових станiв, а також квантовi фазовi переходи першого i другого порядку мiж цими фазами.